PERAN BADAN MEDIASI DAN ARBITRASE ASURANSI INDONESIA (BMAI) : ANALISIS PROSES DAN SIFAT PUTUSAN - LEGOWO, MIG IRIANTO; ZABIDIN, ZABIDIN; WIDYAWATI, AGNES MARIA JANNI (GANEC SWARA, 2023)
The aim of this study is to explore the process of insurance dispute resolution through the Indonesian Insurance Mediation and Arbitration Agency (BMAI) and the nature of its decisions. This research is conducted within the framework of normative juridical legal research, utilizing secondary data as the primary source. The obtained data is then analyzed using a qualitative normative data analysis method. The research findings reveal that the process of settling insurance claim disputes through the Indonesian Insurance Mediation and Arbitration Agency (BMAI) involves three main stages designed to provide effective and efficient alternative dispute resolution. These stages include mediation, adjudication, and arbitration. As for the nature of the decisions made by the Indonesian Insurance Mediation and Arbitration Agency (BMAI), they are considered final and binding. In other words, the final and binding nature of these decisions requires all parties involved in the dispute to adhere to and execute the decisions.